The impact of physical training on neutrophil extracellular traps in young male athletes – a pilot study - Orysiak, Joanna; Tripathi, Jitendra K.; Brodaczewska, Klaudia K.; Sharma, Atul; Witek, Konrad; Sitkowski, Dariusz; Malczewska-Lenczowska, Jadwiga (Biology of Sport, 2021)
Neutrophils are an important component of the innate immune response against various pathogens. However, there is a lack of research concerning the effects of short intensive training on neutrophil functions, especially neutrophil extracellular traps (NET) formation. The study aim was to determine the effects of a 19-day training cycle on innate immunity among young male athletes. Six male ice hockey players (< 20 years old) from the Polish national team were monitored across a five-day training camp and after a return to normal club training. The first blood collection took place before training (T1), the second after the training camp (T2) and the third 14 days later (T3). The counts/concentrations of blood biochemical, immune and endocrine markers were compared across each training period. Creatine kinase activity tended to increase at T2 (546 ± 216 U·L-1) when compared to T1 (191 ± 111 U·L-1; p=0.063). Neutrophil extracellular traps formation and neutrophil counts also differed between training periods (p=0.042 and p=0.042, respectively). Neutrophil counts tended to decrease, in contrast to NET formation which tended to rise, at T2 in comparison to T1 (2.51 ± 0.45 vs 3.04 ± 0.47 109 ·L-1; 24 ± 13 vs 8 ± 15%, respectively). No significant differences in other leucocyte counts were observed. A short period of intensive training was accompanied by some muscle damage and inflammation, as evidenced by CK and NET up-regulation, whilst neutrophil counts were diminished in the blood. Thus, neutrophils and NET could be involved in muscle damage and local inflammatory processes following intensive physical training in young male athletes